Self-Reported Versus Accelerometer-Assessed Daily Physical Activity in Childhood Obesity Treatment. Issue 4 (August 2017) - Schnurr, Theresia M.; Bech, Bianca; Nielsen, Tenna R. H.; Andersen, Ida G.; Hjorth, Mads F.; Aadahl, Mette; Fonvig, Cilius E.; Hansen, Torben; Holm, Jens-Christian
We investigated the relationship between interview-based subjective ratings of physical activity (PA) engagement and accelerometer-assessed objectively measured PA in children and adolescents with overweight or obesity. A total of 92 children and adolescents (40 males, 52 females) with BMI ≥ 90th percentile for sex and age, aged 5–17 years had valid GT3X + accelerometer-assessed PA and interview-assessed self-reported information on PA engagement at the time of enrollment in a multidisciplinary outpatient tertiary treatment for childhood obesity. Accelerometer-derived mean overall PA and time spent in moderate to vigorous physical intensity were generated, applying cut-offs based on Vector Magnitude settings as defined by Romanzini et al. (2014), and a physical activity score (PAS) based on self-reported data. Overall, a higher self-reported PAS was correlated with higher accelerometer-assessed daily total PA levels ( r = 0.34, p < .01) and children who reported a high PAS were more physically active compared with children who reported a low PAS. There was a fair level of agreement between self-reported PAS and accelerometer-assessed PA (Kappa agreement = 0.23; 95% CI = [0.03, 0.43]; p = .01). PAS, derived from self-report, may be a useful instrument for evaluating PA at a group level among children and adolescents enrolled in multidisciplinary obesity treatment.